"If my family is okay, I'm okay": Exploring relational processes of cultural transition. Issue 5 (3rd September 2019) - Ronkainen, Noora J.; Khomutova, Anastasiya; Ryba, Tatiana V.
Abstract : The experiences of athletes who relocate from their home country have recently been in the centre of attention in sport psychology. The present study examined how migrant athletes construct meanings of a new reality and negotiate their life choices within a matrix of relationships and various cultural narratives of sport, career, and family life. We explore the stories of two transnational athletes in very different settings: a professional athlete moving from Western Africa to Scandinavia, and an amateur elite athlete accompanying his professional migrant partner moving from a Scandinavian country to a cosmopolitan Asian capital. Both athletes participated in in-depth life story interviews spanning three sessions, which enabled them to connect the past, present, and future in subjectively meaningful ways. Athletes' migration narratives were explored through the prism of the relational cultural paradigm, and then analysed with respect to three temporal phases of Cultural Transition Model: pre-transition; acute cultural adaptation; and sociocultural adaptation. For both participants, relational contexts were crucial for the successful navigation of cultural transition and transformation of meaning in sport practices. Both athletes constructed their transitions within transnational space, where cultural adaptation was an open-ended process involving multiple belongings and anticipated future mobilities.